The Effect of Nanoencapsulated Citrus sinensis Peel Extract in Drinking Water on Growth Performance of Broiler Chicken - Azmi, Hanggara Haidar; Zuprizal, Zuprizal -; Dono, Nanung Danar; Abdel-Mageed, Ahmad M; Sasongko, Heru -; Ariyadi, Bambang - (Buletin Peternakan, 2024)
This research aimed to investigate the characteristics of nanoencapsulated Citrus sinensis peel extract (NCSPE) applied in drinking water and its effect on broiler chickens' growth performance and jejunal histomorphology. The total of 192 Male Broiler chicken was distributed into six treatments with four replicates (Eight birds each replicate). The experimental  treatments were control diet and drinking water added with no treatment (T0; negative control), tetracycline 50 mg/l (T1; positive control), CSPE (Citrus sinensis peel extract) 1,5% (T2), CSPE 3% (T3), NCSPE 1,5% (T4), and NCSPE 3% (T5). The variables evaluated in this research were characteristics of NCSPE, growth performance. Data were analyzed using ANOVA in a completely randomized design. All data with a significant difference were then tested   again using the Duncan Test with a probability of less than 5%. Results showed  that the size of NEPM was 13,70 nm with a spherical shape and negative charges with zeta potentials of -13.37 mV. Supplementing 1,5% and 3% of NCSPE affects on feed intake, weight gain, and feed conversion ratio. It concluded that both 1,5% and 3% supplementation of NCSPE had a positive effect on growth performances.